Receptor for hyaluronic acid-mediated motility (RHAMM, CD168) expression is prognostically important in both nodal negative and nodal positive large cell lung cancer. Issue 5 (2nd March 2015) - Augustin, Florian; Fiegl, Michael; Schmid, Thomas; Pomme, Geoffrey; Sterlacci, William; Tzankov, Alexandar
Abstract : Objective: Despite advances in therapy, lung cancer is still the leading cause of cancer-related mortality in the world. Further prognostic tools are warranted for risk-adapted therapeutic decisions. We analysed a cohort of primary surgically treated non-small cell lung cancers (NSCLCs) to determine the prognostic role of CD44 and associated molecules (receptor for hyaluronic acid-mediated motility (RHAMM), CD95, osteopontin (OPN), P-glycoprotein (P-gp) and caspase 3 (Casp3)). CD44 is a cell adhesion molecule. While the standard form (CD44s) is ubiquitously expressed, its variant isoforms are claimed to play an important role in invasion and metastasis in various cancers. Methods: Three-hundred and eighty-three primary surgically resected NSCLC specimens were brought into a standardised tissue microarray platform. Immunohistochemistry for CD44, CD95, RHAMM, OPN, P-gp and Casp3 was performed. The clinical correlation was made with known histopathological, phenotypical and genotypical variables; clinical data were available for a postoperative follow-up period of up to 15 years. Results: RHAMM expression in the subgroup of large cell carcinomas (LCC) was associated with inferior survival (p=0.000223). Median overall survival was 92 versus 18 months for RHAMM-negative and positive patients, respectively. This survival difference remained significant in both nodal negative and positive patients (pN0: p=0.013 and pN≥1: p=0.007, respectively). P-gp expression was associated with inferior survival in adenocarcinomas (ACA; p=0.013) and appeared to be a postsurgical Union International Contre le Cancer (pUICC)- stage and gender-independent prognostic factor, irrespective of adjuvant chemotherapy, in the multivariable analysis; considering nodal status, this survival difference applied to pN0 cancers (p=0.026). Conclusions: Analysis of RHAMM expression is a valuable predictor of survival in LCC. RHAMM-positive patients may benefit from a targeted therapy even in early nodal negative stages. Expression of P-gp identifies a subset of pN0 ACA patients with poor outcome independent of stage, gender and adjuvant chemotherapy.